2014
DOI: 10.1158/1078-0432.ccr-14-0072
|View full text |Cite
|
Sign up to set email alerts
|

Reversible LSD1 Inhibition Interferes with Global EWS/ETS Transcriptional Activity and Impedes Ewing Sarcoma Tumor Growth

Abstract: Purpose Ewing sarcoma is a pediatric bone tumor which absolutely relies on the transcriptional activity of the EWS/ETS family of fusion oncoproteins. While the most common fusion, EWS/FLI, utilizes lysine-specific demethylase 1 (LSD1) to repress critical tumor suppressors, small molecule blockade of LSD1 has not yet been thoroughly explored as a therapeutic approach for Ewing sarcoma. We therefore evaluated the translational potential of potent and specific LSD1 inhibition with HCI2509 on the transcriptional p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(189 citation statements)
references
References 65 publications
9
177
3
Order By: Relevance
“…In contrast to previous efforts to inhibit EWSR1-FLI1 activity that have capitalized on individual target gene expression or physical interactions (31)(32)(33)(34)(35)(36), the application of HT-FAIRE offered a strategy to identify therapeutics based on variation in chromatin accessibility, a universal genomic feature determined by the combined effects of transcriptional regulators and chromatin regulatory proteins (37). Indeed, FAIRE has been shown to detect specific chromatin changes resulting from treatment with anthracyclines that directly interact with DNA (38,39), thereby demonstrating the utility of this assay to explore the function of small molecule compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous efforts to inhibit EWSR1-FLI1 activity that have capitalized on individual target gene expression or physical interactions (31)(32)(33)(34)(35)(36), the application of HT-FAIRE offered a strategy to identify therapeutics based on variation in chromatin accessibility, a universal genomic feature determined by the combined effects of transcriptional regulators and chromatin regulatory proteins (37). Indeed, FAIRE has been shown to detect specific chromatin changes resulting from treatment with anthracyclines that directly interact with DNA (38,39), thereby demonstrating the utility of this assay to explore the function of small molecule compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we identified additional components of this complex in our initial proteomic screen, namely RBBP7, MTA2, GATAD2A, GATAD2B, HDAC1, and HDAC2, suggesting that PAX3-FOXO1 might indeed interact with the NuRD complex. It has been demonstrated that this remodeling complex is also required for EWS-FLI1-mediated transcriptional repression (50), and inhibition of LSD1 using small-molecule inhibitors impaired Ewing sarcoma cell viability (51). Hence, we next thought to identify components of the complex that might be necessary for PAX3-FOXO1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of the N-terminal region of EWSR1, which contains a strong transcriptional activation domain [21,22] , and these DNA binding domains causes aberrant transcription of a multitude of genes. Additionally, EWSR1-ETS is known to affect epigenetic programs [23,24] , splicing [25,26] , and metabolic activity [27] of EWS. Oncogenic fusions between ETS genes and transcriptional activators are not unique to EWS: in 50%-70% of prostate cancers, similar chromosomal rearrangements are found [28] .…”
Section: Chromosomal Translocationsmentioning
confidence: 99%
“…Targeting the fusion protein directly has proven to be challenging due to its flexibility, but progress has been made and a phase I clinical trial (NCT02657005) is ongoing with a small molecule inhibitor [108] . Aside from targeting the EWSR1-ETS fusion protein directly, inhibiting its dominant direct targets has been investigated as therapeutic alternative, as EWSR1-ETS is a key driver in the epigenetics [23,24] , transcription [109] , splicing [25,26] , and metabolic [27] reprogramming of EWSR1-ETS.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%